2020
DOI: 10.1186/s13643-020-01367-w
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the prevention and management of occupational stress injury in first responders: a rapid overview of reviews

Abstract: Background: First responders are a high-risk population for occupational stress injuries as they often encounter prolonged stress within their line of work. The aim of this rapid overview of reviews is to summarize existing evidence on interventions for the prevention and management of occupational stress injury (OSI) in first responders. Methods: MEDLINE, EMBASE, PsycINFO, CINAHL, Web of Science, and Cochrane Library were searched for systematic reviews examining the impact of prevention, rehabilitation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…The need for evaluative studies of post‐disaster mental health interventions has been well documented, 3 and the difficulties in their design thoughtfully described 4,5 . Two systematic reviews, 6,7 including evidence from small randomized trials, 8–10 concluded that primary prevention strategies had some impact but that the effect of post‐event interventions was uncertain. Early attempts focused on post‐incident debriefing and early psychological interventions, which were found not to be useful in the secondary prevention of posttraumatic stress disorder (PTSD) 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…The need for evaluative studies of post‐disaster mental health interventions has been well documented, 3 and the difficulties in their design thoughtfully described 4,5 . Two systematic reviews, 6,7 including evidence from small randomized trials, 8–10 concluded that primary prevention strategies had some impact but that the effect of post‐event interventions was uncertain. Early attempts focused on post‐incident debriefing and early psychological interventions, which were found not to be useful in the secondary prevention of posttraumatic stress disorder (PTSD) 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…While greater attention to operational stressors in police work is understandable given their dramatic nature and undeniable adverse impacts, there has been a relative neglect of organizational stressors in research, policy, and practice. In conclusion, we would argue that despite the challenges of getting police departments and their funders (in the context of this study, the state government) to earnestly address organizational stressors, this remains an essential priority for workplace mental health in policing contexts and deserves on‐going attention in research, policy, and practice 1,11 …”
Section: Discussionmentioning
confidence: 87%
“…A wide range of stress reduction interventions have been implemented and evaluated in policing/law enforcement contexts, as summarized in a recent umbrella review of interventions for the prevention and management of occupational stress injury in the first responders 11 . This review focused on mental health outcomes and detailed findings from 47 primary studies, categorized into prevention (24 primary studies, 21/24 in police settings) and rehabilitation interventions (23 primary studies, 16/23 in police settings).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations